2019
DOI: 10.1177/8756972819869091
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous Program Management: The Case of Autonomous Mobility

Abstract: This article analyzes the management of project portfolios that encompass both exploratory and implementation projects under the denomination of ambidextrous program management. We build on the project/program and ambidexterity literature to characterize such programs. Based on an in-depth three-year study, we apply this analytical framework to an emblematic case: the Autonomous Mobility (AM) initiative of a major automotive firm. We characterize the coordination challenges of such ambidextrous program managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…In particular, we encourage future research on decision makers’ personality traits (McNally et al, 2009), their cognitive load (Killen et al, 2020), and influences of status reporting (Hopmere et al, 2020) in relation to ROR. Finally, we see great potential in exploring the organizational change process ROR could support over time (Midler et al, 2019). Depending on the actual selection of executed options, projects could either contribute to the originally intended strategy or support the development of new emerging strategies (Bowman & Hurry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we encourage future research on decision makers’ personality traits (McNally et al, 2009), their cognitive load (Killen et al, 2020), and influences of status reporting (Hopmere et al, 2020) in relation to ROR. Finally, we see great potential in exploring the organizational change process ROR could support over time (Midler et al, 2019). Depending on the actual selection of executed options, projects could either contribute to the originally intended strategy or support the development of new emerging strategies (Bowman & Hurry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, all the analyzed companies indicated that hybrid management is ideal for innovative projects, those involving a high amount of uncertainty and that cannot be undertaken without some level of planning because of the constraints of the organizational environment or the business sectors (Martinsuo, 2019; Midler et al, 2019). In alignment with the results presented in SLR, suitable projects for adopting hybrid management include research and development of new technologies with innovative character and involving high levels of complexity, risks, and uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that theory-building research usually combines multiple data collection methods (Eisenhardt, 1989), this article combines multiple case studies in an exploratory way. This method is applied in exploratory research (Dingsøyr et al, 2018; Liu et al, 2019; Midler et al, 2019; Momeni & Martinsuo, 2019), starting with the formulation of the research question related to the emerging phenomenon in order to build knowledge capable of contributing to the academic discourse (Müller & Klein, 2019). Cooper and Sommer (2016) investigated publications that described cases of agile applications and highlighted studies with multiple case studies, a relevant method because multiple case studies allow cross-case analyses and the triangulation of obtained evidence, making it possible to look beyond impressions and to obtain evidence considering multiple perspectives, improving the levels of analysis, providing substantial foundations for hypotheses and constructs, and enhancing confidence (Eisenhardt, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Reference to 'project level' implies the scope of activities undertaken during and within projects. It is at this level that strategy is orchestrated (Chipulu et al 2016;Kopmann et al 2017;Maylor et al 2018;Midler, Maniak, and de Campigneulles 2019) and value created by organizations (Parvan, Rahmandad, and Haghani 2015). Projects are the ideal means of delivering strategies in that they are the primary conduit for acquiring, integrating, developing, re-arranging and deploying the entire spectrum of an organizations assets, competencies and capabilities (Narayanan andDeFillippi 2012, Turner andLee-Kelley 2013;Turner, Maylor, and Swart 2015;Petro et al 2019Petro et al , 2020.…”
Section: Rbv Theory and The Organizationmentioning
confidence: 99%